Perancangan Media Pembelajaran Mengenal Huruf Arab (Hijaiyah) untuk Anak Usia 4-6 Tahun dengan Menggunakan Software Pengolah Animasi 2 Dimensi - Andini, Titania Dwi; Wafa, Achmad Bahar (Jurnal Desain Komunikasi Visual Asia, 2017)
This learning media is very useful because it helps Children at 4-6 years of age can more easily receive the material that is taught in addition to also make the children interested to learn the material delivered. In this learning media will be delivered is about the Arabic Letters (Hijaiyah) . More aimed at children at 4-6 years old, because in children aged 4-6 years is very easy and quick to memorize from what they see and learn. The sophistication of technology now allows anyone to learn to make learning media such as 2-dimensional animation processing software, Macromedia Flash and vector image processing software, Corel Draw. This learning media has an interesting concept, from the material it conveys easily understood, coupled with unique character and background image will make the children unsaturated to learn it and understand the contents of the material presented.